COLLEMBOLA DIVERSITY IN FORMER TRADITIONAL GOLD MINING IN SAMPOINIET DISTRICT, ACEH JAYA REGENCY - Rizky Ahadi; Ernilasari Ernilasari; Cut Nadia Rahmi (Universitas Islam Negeri Ar-Raniry, 2021)
Collembola functions as a bio-indicator of soil fertility, while maintaining the stability of nutrients and oxygen which are very beneficial for plants. However, the Collembola diversity in its habitat could be affected by mercury waste. This study aims to determine the diversity of Collembola species in the former mercury waste storage area of traditional gold mining in Ligan Village, Sampoiniet District, Aceh Jaya Regency. This research was conducted in June-July 2019 in 6 (six) locations in the former mercury waste storage area in Ligan Village, Sampoiniet District, Aceh Jaya Regency. The sampling was done by purposive sampling method using pitfall trap. Data were collected by comparing the morphological characteristics of Collembola by referring to Boror's (1996) identification book and analyzed with Diversity Index of Shannon Winner. There are 5 Collembola species found in the research location with Diversity Indek H '= 1.485323798 in the medium category. Mercury average levels found in the study site have exceeded the crisis concentration threshold with the value of 0.5111 mg/kg, which is assumed affecting the diversity of Collembola species in its habitat.